Setting priorities for public spending - International Food Policy Research Institute (International Food Policy Research Institute, 2015)
Public investment in agriculture and in rural areas plays a pivotal role in increasing productivity and reducing poverty. Knowing which investments will have the most impact helps developing countries spend strategically. IFPRI has been a leader in providing this information.